Lost at Sea? Navigate! Using Metrics and Results to Establish the Value of Communications and Knowledge in Sanitation and Water Service Delivery - Walsh, Christopher (World Bank, Washington, DC, 2012)
The communications and knowledge work of the World Bank Group takes many shapes; and although one commonality is its enhancement and support of the institutional mission and development objectives, communications and knowledge work is not always subject to monitoring processes as is the case with its operations counterpart. Similar to a ship's captain navigating by starlight, communications and knowledge work can be well guided by undefined indicators and tacit knowledge of what successful communications campaigns and knowledge management look like; however, if there were ever a time to develop and use more precise navigational instruments, now is that time. This smart lesson explores how the Water and Sanitation Program (WSP), a global partnership administered by the World Bank, developed such navigational instruments for communications and knowledge. By explicitly tying communications and knowledge activities to development objectives and taking time to identify, aggregate, and monitor outputs, qualitative and quantitative indicators, and assumptions, WSP helped quantify the contribution of communications and knowledge to the achievement of the program's business and development objectives.